PERIOD BEFORE WEED INTERFERENCE AND YIELD COMPONENTS IN TRANSGENIC SOYBEANS AS A FUNCTION OF SOWING METHODS - SILVA, Alexandre Ferreira; GALON, Leandro; REIS, Marcelo Rodrigues; ROCHA, Paulo Roberto Ribeiro; FERREIRA, Evander Alves; TIRONI, Siumar Pedro; ASPIAZU, Ignacio; SILVA, Antônio Alberto (Scientia Agraria, 2009)
The aim of this study was to evaluate the influence of no-tillage and conventional tillage systems over the period before weed interference (PBI) and the effects on the soybean cv. BRS 243-RR yield components. The experimental design was arranged in completely randomized blocks, and the treatments consisted of increasing periods of control (0, 5, 10, 15, 21, 28, 35, 42, 49 e 125 days). The conventional tillage weed community was composed mainly by Brachiaria plantaginea, Ipomoea sp., Digitaria horizontalis and Cyperus rotundus; in no-tillage, Brachiaria plantaginea, Euphorbia heterophylla, and Ipomoea sp. were the most frequent weeds. The conventional tillage showed higher population and dry mass of weeds during the assessment period. Regarding to the crop yield components, number of pods per plant was the most severely affect by competition; number of seeds per pod and weight of thousand grains were less affected by competition. Considering 5% of tolerance on soybean grain yield reduction, the period before interference happened 12 days after emergence (DAE) in the conventional tillage system and 17 DAE in no-tillage. The weed interference during the full crop cycle reduced soybean grain yield in 74% in the conventional tillage and 63% in no-tillage.